A Daily Life Content Analysis on the Kinderflix Youtube Channel as a Means of Imitating Early Childhood Adaptive Behavior: english - Kanisa Dewi Suci Lestari; Nurdiansyah Nurdiansyah; Gia Nikawanti (Jurnal Pendidikan Terapan, 2026)
Purpose: In the digital era, visual media acts as a "third classroom" influencing early childhood development. This study analyzes the effectiveness of Kinderflix’s daily life content as a medium for imitation in shaping adaptive behaviors, including self-help, communication, social-emotional, and motor skills. Methods: This qualitative research employs content analysis. Data were collected from six popular daily lifevideos via purposive sampling. The observation instrument was structured based on Albert Bandura’s Social Learning Theory, focusing on the phases of attention, retention, motor reproduction, and motivation. Data validity was ensured through triangulation of sources and theories. Findings: Findings indicate that Kinderflix methodically applies modeling principles through multisensory stimulation. Strategies include: (1) repetitive articulation and expressive gestures for attention; (2) interactive songs as mnemonic tools for retention; (3) invitations for active participation for motor reproduction; and (4) vicarious reinforcement for motivation. This content systematically builds adaptive behavior structures, fostering independence and social responsiveness. Research implications: Kinderflix serves as an effective adaptive educational instrument rather than mere passive entertainment. This study highlights the necessity of parental roles as active mediators to facilitate the transition from digital information to real-life action. Originality: The uniqueness of this research lies in proving how local Indonesian content, such as Kinderflix, can turn digital viewing into real action for children. At a time when similar research is still rarely done in Indonesia, this study is here to explain in depth how the video works in shaping children's independence and social skills through real human examples.